Proceedings of the 42nd Annual Conference on Design Automation - DAC '05 2005
DOI: 10.1145/1065579.1065653
|View full text |Cite
|
Sign up to set email alerts
|

Keeping hot chips cool

Abstract: With 90nm CMOS in production and 65nm testing in progress, power has been pushed to the forefront of design metrics. This paper will outline practical techniques that are used to reduce both leakage as well as active power in a standard-cell library based high-performance design flow. We will discuss the design and cost issues for using different power saving techniques such as: power gating to reduce leakage, multiple and hybrid threshold libraries for leakage reduction and multiple supply voltage based desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 10 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…To keep hot chips cool, the more the integration on a single die the more holistic power minimisation approaches are required across the whole design stack [19]. The power‐aware approach we are presenting combines structural and dynamic aspects.…”
Section: Introductionmentioning
confidence: 99%
“…To keep hot chips cool, the more the integration on a single die the more holistic power minimisation approaches are required across the whole design stack [19]. The power‐aware approach we are presenting combines structural and dynamic aspects.…”
Section: Introductionmentioning
confidence: 99%
“…For microprocessors, it is a well-known fact that the clock distribution network including the clocked elements (e.g. latches, flip-flops and macros) consumes a majority of the total dynamic power, because the clock network usually switches during every clock cycle [22,50]. Studies [20,55] have shown that the leaf level of the clock tree, i.e., nets driving the clocked elements (hereafter referred to as latches), is a major power consumer among the entire clock distribution network.…”
Section: Placement Results On the Ispd-2006 Benchmarksmentioning
confidence: 99%
“…In being driven by this LCB. Results in [50] show that this design style can significantly reduce the capacitive load on the clock signals driven by the LCBs, and also improve timing.…”
Section: Previous Work On Local Clock Tree Synthesis Methodologymentioning
confidence: 99%
See 2 more Smart Citations